Surgical Treatment of Functional Mitral Regurgitation Involving the Subvalvular Apparatus. Issue 1 (23rd October 2014) - Kato, Yasuyuki; Bando, Ko; Fukui, Toshihiro; Mahara, Keitaro; Takanashi, Shuichiro
Abstract Background and aim of the study We retrospectively studied outcomes after mitral annuloplasty (MAP) combined with subvalvular procedures for patients with functional mitral regurgitation and ischemic dilated cardiomyopathy. We focused on changes in mitral regurgitation (MR) grade, mitral valve tethering, and left ventricular (LV) volume before and after surgery. Methods Thirty‐one patients underwent MAP combined with subvalvular procedures including papillary muscle (PM) approximation, PM relocation, and chordal cutting. Fifteen patients underwent left ventriculoplasty. Twenty patients underwent PM approximation, and 11 patients underwent PM relocation. Two patients underwent chordal cutting in addition to PM approximation or relocation. In 25 patients, echocardiographic measurements of MR grade, mitral valve tethering, and LV volume were compared among three time points: before, immediately after, and one year after surgery. Results There were no in‐hospital deaths. LV volume as well as both tenting height and area were significantly reduced immediately after and at one year after surgery. Five patients developed recurrent MR at one year after surgery. In comparison with the other 20 patients, the preoperative MR grade was significantly higher (p = 0.018). The postoperative reduction of LV volume was significant in patients without recurrent MR. Conclusions Both tenting height and area could be significantly reduced and maintained after MAP combined with subvalvular procedures. The preoperative MR grade and the presence of a large postoperative LV volume were more likely to result in recurrent MR. However, among patients with recurrent MR, the MR grade does not increase during mid‐term follow‐up. doi: 10.1111/jocs.12459 (J Card Surg 2015;30:27–34)